Laparoscopic cholecystectomy in a resource limited setting: Factors associated with difficult surgeries at the National Referral Hospital, Bhutan - Sangay Wangmo; Sonam Dargay; Sonam ChhodenR (Wiley, 2023)
Abstract Background Prediction of difficult laparoscopic cholecystectomy may help in making necessary arrangements for optimal intraoperative requirements and postoperative care. This study was conducted to examine the factors associated with and outcomes of difficult laparoscopic cholecystectomy performed at the Bhutan's largest hospital in 2020. Methods This was a cross‐sectional study with a convenience sampling method. Data on clinical features, ultrasonography and intraoperative factors of patients who underwent laparoscopic cholecystectomy were extracted from their medical records, investigation reports and intraoperative surgery note. Difficult laparoscopic cholecystectomy was defined on the basis of the duration of the surgery, injury to bile duct or artery, or conversion to open cholecystectomy. Data were double entered and validated in EpiData 3.1 and analysed in STATA 13.0. Results Data from 134 patients were extracted. The mean age of the sample was 43 (±SD 13) years. "Difficult laparoscopic cholecystectomy" was reported in 83 patients (62%) and easy laparoscopic cholecystectomy in 51 patients (38%). Those patients having simple adhesions up to the body of the gall bladder were 1.6 times more likely to encounter difficult laparoscopic cholecystectomy (adjusted PR = 1.60, 95% CI 1.04-2.48, p = 0.034). The majority did not have any post‐operative complications (130 cases, 97%). The indications of laparoscopic cholecystectomy were symptomatic gall stone disease (129, 96%), acalculous cholecystitis (2, 1%) and gall bladder polyp (3, 2%). Conclusions The proportion of difficult laparoscopic cholecystectomy is high, but the rates of post‐operative complications were minimal with no mortality or injury to bile duct or arteries.